A thiomethyl-substituted imidazolyl imine functionalized copper(II) complex: synthesis, structural characterization, phenoxazinone synthase mimics and biological activities. (15th May 2022) - Bandopadhyay, Nilaj; Paramanik, Krishnendu; Mudi, Prafullya Kumar; Sarkar, Gayetri; Kotakonda, Muddukrishnaiah; Shit, Madhusudan; Biswas, Bhaskar; Sankar Das, Hari
Graphical abstract: Abstract: A cis -dichloro copper(II) complex with a novel tridentate thiomethyl substituted imidazole based Schiff base ligand L, obtained from 2-methylthioaniline and 2-imidazolecarboxaldehyde, has been synthesized and characterized by spectroscopic methods and X-ray crystallography. The crystal structure of the complex shows a distorted square-pyramidal environment around the copper(II) centre, coordinated by the tridentate ligand L and two cis -chloride ligands (one axial and another equatorial). The supramolecular framework, connected through several intermolecular noncovalent interactions in the crystal structure, has been investigated in detail. The complex effectively shows phenoxazinone synthase-like activity (aerial oxidation of 2-aminophenol to 2-amino-phenoxazine-3-one) under ambient conditions with a high turnover number of 1.92 × 10 4 h −1 . Further, the antimicrobial activity of the copper(II) complex was examined against E. coli, Staphylococcus aureus and K. pneumoniae clinical microbial cultures, which imply its significant bactericidal property compared to the standard antibiotic agent ciprofloxacin . In addition, the anticancer activity of the copper(II) complex was tested against the human colorectal adenocarcinoma (HT-29) cancerous cell line and it shows notable activity with an IC50 value of 125 μg mL −1 .